Peculiarities of the Tail-Withdrawal Reflex Circuit in Aplysia: a Model Study - Ye, W.; Liu, S.Q.; Zeng, Y.J. (Нейрофизиология, 2013)
The circuit of the tail-withdrawal reflex in Aplysia opens up possibilities to construct model systems allowing researchers to effectively investigate simple forms of learning and memory. Using the Python interface of the NEURON software, we simulated this reflex circuit and studied various characteristics of the latter. The phenomenon of spike frequency adaptation (SFA) and the period-adding bifurcation of the minimum were found in sensory neurons, when the latter were stimulated by square-wave stimuli. In all neurons of the circuit, variation of the stimulus strength first increased and then decreased the number of spikes in a burst. In addition, with decreases in the number of stimulated sensory neurons, a subliminal firing other than that in an intact burst appeared at the outputs of interneurons and motor neuron. Moreover, the potentials produced in the motor neuron induced corresponding oscillations of the muscle fiber force, which was indicative of a procedure of excitement-contraction coupling in the tail part of Aplysia. Finally, upon alteration of the conductance of synapses between interneurons and motoneuron, the duration of long-lasting responses increased regularly, implying synaptic plasticity